Penambahan Berat Sic Pada Komposit Matrik Aluminium Dalam Sifat Fisis Dan Mekanis Diperkuat Tib Sebagai Penghalus Butir - Lilin Hermawati; Sunu Arsy Pratomo; Sugeng Hariyadi (Pusat Riset dan Inovasi Nasional, 2023)
Aluminum is an excellent material for making composites because it is lightweight, ductile, does not corrode easily and is easier to shape and fabricate. Various properties of existing aluminum, aluminum has mechanical properties that are not good, namely very low hardness. In a good method for processing aluminum, namely stir casting, why is this method used because it is quite cheap and easy to process by means of an alloy that is heated with an adjusted heat and stirred to mix all the existing composite materials and given reinforcement or grain refiner to obtain a good and evenly distributed composite metric without reducing the function of the existing composite. The method used in this study serves to improve the mechanical properties of a metal and SiC is used as a reinforcement and TiB is used as a grain refiner. SiC has advantages over other ceramic materials, namely it bonds easily with aluminum and does not cause oxidation of aluminum metal. Increasing the wetability of metal alloys with reinforcement, the technique used is by stirring when the liquid metal is in a semisolid phase. This research focused on variations in weight percent SiC powder 0%, 5%, 7.5%, and 10% and the addition of 5% Tib. To determine the physical and mechanical properties of the Al-SiC-TiB composite, several tests were carried out, namely density, porosity, hardness, bending and microstructure tests. The results of the tests showed that the highest density value was found at 0% SiC by weight at 2.70 gr/cm3, the lowest at 10% SiC at 2.65 gr/cm3. Porosity calculations show that the highest porosity value is found in 10% SiC by weight of 3.16%. The highest hardness test result was 10% SiC by weight at 72.6 HRB and the bending test result with the highest hardness value at 10% SiC by weight was 371.5 MPa. The test results show that the mechanical properties increase with the increase in the percentage of SiC powder up to 10% and with the addition of TiB the finer grains are produced so that the porosity decreases.